Campus Medius: Digital Mapping in Cultural and Media Studies - Ganahl, Simon (Digital Humanities, 2022)
Campus Medius explores and expands the possibilities of digital cartography in cultural and media studies. Simon Ganahl documents the development of the project from a historical case study to a mapping platform. Based on the question of what a media experience is, the concepts of the apparatus (dispositif) and the actor-network are translated into a data model. A time-space of twenty-four hours in Vienna in May 1933, marked by a so-called »Turks Deliverance Celebration« (Türkenbefreiungsfeier), serves as an empirical laboratory. This Austrofascist rally is mapped from multiple perspectives and woven into media-historical networks, spanning from the seventeenth century up to the present day.